Cultural Representation on The Functional Grammar Exercises in an Indonesian Junior High School English Textbook - Fauzi, Ashar; Dewi, Tiara Ayu Kusuma (Journal of English Education Program, 2024)
Studies on English language textbook analysis rarely incorporate cultural values in the functional grammar exercises since it is a crucial learning material in the English textbook. To address this gap, we aim to pinpoint the representation of cultural values in the functional grammar exercises in an Indonesian junior high school English textbook. By employing critical discourse study as the research methodology, we analyzed both the visual and textual data presented on the functional grammar exercises in the textbook. We adopted two analytical tools for analyzing data, i.e. transitivity analysis; and critical discourse analysis. The result shows that there are 28 functional grammar exercises that facilitate students in making meaning. Meaningful cultural representation from many social practices was found. This study suggests incorporating its findings into teaching to explain cultural values to students. Further studies need to focus on providing teacher experiences in teaching functional grammar exercises.